Power Management Strategy Based on Adaptive Droop Control for a Fuel Cell-Battery-Supercapacitor Hybrid Tramway - Li, Qi; Wang, Tianhong; Dai, Chaohua; Chen, Weirong; Ma, Lei (IEEE transactions on vehicular technology, 2018)
In order to coordinate multiple power sources appropriately, and avoid the transients and rapid changes of power demand, a power management strategy based on an adaptive droop control, which is combined with a multimode strategy and an equivalent consumption minimization strategy, is proposed for a large-scale and high-power hybrid tramway. According to the hybrid system model of tramway developed with commercially available devices, the proposed power management strategy is evaluated with a real driving cycle of tramway. The results obtained from RT-LAB platform testify that the proposed strategy is able to manage and coordinate multiple power sources based on their natural characteristics, maintain dc bus voltage stabilization, improve the efficiency of overall tramway, and alleviate the stress on the hybrid power system.